A 20th anniversary perspective on the life of RAFT (RAFT coming of age). Issue 8 (18th December 2019) - Moad, Graeme; Rizzardo, Ezio
Abstract: RAFT (reversible addition–fragmentation chain transfer) polymerization, making use of thiocarbonylthio transfer agents, was announced to the world just over 21 years ago. RAFT arose out of a desire to achieve perfection in polymers (or at least to define and limit the imperfections) and to invent living radical polymerization. However, living radical polymerization cannot be and never was. This perspective looks at RAFT after 21 years of development. Is RAFT a mature technology? We briefly summarize areas of current interest focusing on what is happening at CSIRO and point to where RAFT is going in areas such as RAFT free from exogenous initiators (photoRAFT, PET‐RAFT, eRAFT), new RAFT agents, RAFT for sequence‐defined polymers and RAFT single unit monomer insertion, RAFT emulsion polymerization and RAFT polymerization‐induced self‐assembly (PISA), RAFT‐crosslinking polymerization and the industrial applications of RAFT. © 2019 Society of Chemical Industry Abstract : Where is RAFT going? RAFT free from exogenous initiators, new RAFT agents, RAFT for sequence‐defined polymers, RAFT emulsion polymerization and RAFT polymerization‐induced self‐assembly, RAFT‐crosslinking polymerization and the industrial applications of RAFT.